1997
DOI: 10.1253/jcj.61.1015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Volume Loading on Pulmonary Venous Flow and its Relation to Left Atrial Functions

Abstract: Although pulmonary venous (PV) flow is closely related to left atrial (LA) pressure dynamics, few investigators have discussed it in relation to LA functions, i.e., reservoir, conduit, and booster pump functions. We examined changes in PV flow rate, LA dimension, and left ventricular filling volume in 11 dogs, and assessed the effects of multistaged volume loading on PV flow and LA functions. Systolic PV flow rate (S) increased significantly and reached a plateau, reflecting a limited LA reservoir function. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
13
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…33 Also, healthy dogs have fewer β-adrenergic receptors in the left atrium than in the left ventricle 34 ; thus, the negative inotropic and lusitropic effects of esmolol on the left atrium might have been inadequate to cause a significant decrease in left atrial function, especially in the presence of the concurrent drug-induced effects on the left ventricle. 6,24,29 Indeed, in the present study, a decrease in venous return following milrinone administration was supported by a decrease in LVID d . Although milrinone, like dobutamine, has positive inotropic and lusitropic actions, 16,21-23 its administration did not significantly affect left atrial phasic function in the dogs of the present study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…33 Also, healthy dogs have fewer β-adrenergic receptors in the left atrium than in the left ventricle 34 ; thus, the negative inotropic and lusitropic effects of esmolol on the left atrium might have been inadequate to cause a significant decrease in left atrial function, especially in the presence of the concurrent drug-induced effects on the left ventricle. 6,24,29 Indeed, in the present study, a decrease in venous return following milrinone administration was supported by a decrease in LVID d . Although milrinone, like dobutamine, has positive inotropic and lusitropic actions, 16,21-23 its administration did not significantly affect left atrial phasic function in the dogs of the present study.…”
Section: Discussionsupporting
confidence: 62%
“…Phenylephrine is an α 1 adrenergic receptor agonist with vasoconstrictive effects 28 and was selected because its effects were expected to contrast with those of milrinone. 6 Additionally, an increase in the blood volume of venous return (ie, left atrial preload) will enhance all 3 left atrial phasic functions, 6,24,29 and it is possible that drug-induced changes in left atrial intrinsic contractility and relaxation will not affect the indices of left atrial phasic function. The reservoir function is modulated by left ventricular contraction that leads to descent of the left ventricular base, right ventricular systolic pressure that is transmitted through the pulmonary circulation, and intrinsic left atrial intrinsic relaxation and chamber stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…The E/A ratio, which is obtained using the ratio of the early diastolic velocity (E wave) to the late diastolic velocity (A wave) derived from TMF, which indicate LV diastolic function [5,7,8,29,32]. However, it is well-known that TMF profiles are limited because of pseudonormalization.The PVF velocity profile is obtained using waveform relaxation during ventricular systole and early diastole, which indicates atrial function [20,24,25,31]. Several studies have reported that PVF profiles should provide additional information for predicting cardiac function and prognosis in patients with LV dysfunction [14,15,18,19,31].…”
mentioning
confidence: 99%
“…Several studies have reported that PVF profiles should provide additional information for predicting cardiac function and prognosis in patients with LV dysfunction [14,15,18,19,31]. The PVF patterns are closely related to LV diastolic function, left atrial pressure, and other cardiac dynamics [1,5,6,20,22]. However, the basic implication of PVF for evaluating LV diastolic function in normal dogs is still unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation